2016
DOI: 10.1111/eip.12327
|View full text |Cite
|
Sign up to set email alerts
|

Social anhedonia and gamma band abnormalities as a composite/multivariate endophenotype for schizophrenia: a dense array EEG study

Abstract: We propose region-specific high gamma spectral 'power and coherence' and social anhedonia as composite/multivariate measures could be a useful measure in distinguishing schizophrenia patients and unaffected siblings from healthy controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 49 publications
0
1
0
1
Order By: Relevance
“…It appears across all phases of schizophrenia-spectrum disorders, including the prodromal phase (e.g., Jhung et al, 2016). Findings from patients (e.g., Blanchard et al, 2001;Ritsner et al, 2018), first-degree relatives of patients with schizophrenia (e.g., Docherty and Sponheim, 2014;Umesh et al, 2018), and psychometrically identified schizotypes (e.g., Gooding et al, 2005) provide compelling evidence that social anhedonia is a trait-related symptom for many individuals within the schizophrenia spectrum. Thus, evaluating social anhedonia can be crucial in terms of understanding contributory aspects underlying schizophrenia-spectrum disorder.…”
Section: Introductionmentioning
confidence: 99%
“…It appears across all phases of schizophrenia-spectrum disorders, including the prodromal phase (e.g., Jhung et al, 2016). Findings from patients (e.g., Blanchard et al, 2001;Ritsner et al, 2018), first-degree relatives of patients with schizophrenia (e.g., Docherty and Sponheim, 2014;Umesh et al, 2018), and psychometrically identified schizotypes (e.g., Gooding et al, 2005) provide compelling evidence that social anhedonia is a trait-related symptom for many individuals within the schizophrenia spectrum. Thus, evaluating social anhedonia can be crucial in terms of understanding contributory aspects underlying schizophrenia-spectrum disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Moc widmowa wysokiego pasma gamma (> 70 Hz) była znacznie niższa w prawym rejonie skroniowo-ciemieniowym i środkowej linii zarówno w SZ, jak i SB, niż w HC. Autorzy zaproponowali specyficzną dla regionu "moc i koherencję" widma gamma o wysokiej częstotliwości oraz anhedonię społeczną jako miary złożone, wieloczynnikowe, które mogą być użyteczne w odróżnianiu pacjentów ze schizofrenią i zdrowego rodzeństwa od osób zdrowych [34].…”
Section: Inne Problemy Badawczeunclassified